Role Incongruence and Psychological Stress Symptoms in Substitute Decision Makers of Intensive Care Patients. - Smith, Orla M.; Metcalfe, Kelly; Puts, Martine; McDonald, Ellen; Sue-Chee, Shivon; Friedrich, Jan O. (American Journal of Critical Care, 2020)
Background: Most intensive care patients require substitute decision makers (SDMs) to make decisions. The SDMs may prefer an active, shared, or passive decision-making role. Role incongruence is when preferred and actual roles differ. Objective: To evaluate the impact of decision-making role preferences and role incongruence on psychological distress symptoms in SDMs. Methods: A multicenter, interviewer-administered survey was conducted among SDMs of critically ill adults. The Control Preferences Scale was used to evaluate role preferences. Psychological distress was defined as anxiety, depression, or posttraumatic stress symptoms with predefined cut points on the Hospital Anxiety and Depression Scale (score > 10 on the anxiety or the depression subscale) and Impact of Events Scale (score > 30). Results: One hundred eighty SDMs were recruited; 64% responded. Most were white (71%) and female (65%); 46% were spouses. Role preferences varied: active, 24%; shared, 44%; and passive, 31%. Almost half (49%) reported incongruence. Symptom prevalence was 50% for posttraumatic stress, 32% for anxiety, and 16% for depression. Most (56%) reported some psychological distress. In multivariable logistic regression, the composite outcome of psychological distress was independently associated with patient death (odds ratio, 2.95; 95% CI, 1.08-8.02; P =.03), female sex of SDM (odds ratio, 2.96; 95% CI, 1.49-5.89; P =.002), and incongruence (odds ratio, 3.26; 95% CI, 1.67-6.36; P <.001). Conclusions: Adverse psychological symptoms are prevalent in SDMs of critically ill patients and are related to role incongruence.